PENGARUH REALISASI PENDAPATAN PAJAK DAERAH DAN PENDAPATAN RETRIBUSI TERHADAP TINGKAT PENGANGGURAN DENGAN DIMODERASI OLEH BELANJA MODAL - TAMA, ANNAFI INDRA (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2016)
This research aims to find out about the effect of the realization of local tax and levies revenues to the unemployment and moderated by capital expenditure in 33 provinces in Indonesia. Audited Financial statement of 33 Province for period 2013 to 2015 are used in this research. Using moderated regression analysis, the results showed only levies are a significant negative effect to the unemployment while local taxes and capital expenditure has no effect to unemployment. Capital spending could not moderate the effect of local taxes and levies to unemployment.